Analisis Biaya Ekonomi Serta Dampak Lingkungan Penggunaan Gasoline dan Biofuel Sebagai Bahan Bakar Transportasi - Dinanti, Prisila; Sundari, Sri; Laksmono, Rudy; Ramadhan, Try Ridho; Sianipar, Leo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Global warming is not the newest issue we are facing. Until now, the issue of global warming is still a topic of discussion among world-class researchers. Global warming is the increase in the earth's temperature or the average temperature of the atmosphere, sea and earth's land that we are experiencing today. The amount of carbon obtained at this time is the result of industrial, transportation, household and commercial activities in the use of energy consumption. In order to suppress rising temperatures, the government has made the decision to continue its commitment to reducing greenhouse gas emissions by taking a number of strategic steps in the management of the energy, transportation and energy sectors. The government's strategy in the transportation sector is to transition oil-fueled vehicles into electric motorized vehicles. The strategic step to reduce fossil energy consumption is to increase the production of environmentally friendly energy such as bioethanol. However, mixing bioethanol as an environmentally friendly alternative fuel faces problems. Related to the obstacles that become obstacles due to the relatively high cost of bioethanol production, resistance from local entrepreneurs, and limited supply. This writing is by applying the Literature Review method. Literature review contains descriptions of theories, findings and other research materials derived from reference materials as the basis for research activities. In terms of economic and environmental aspects, the use of bioethanol in vehicle fuel can be an alternative solution that must be continuously developed and produced. Keywords: Biofuels, Economic Costs, Gasoline, GHG Emissions, Environment.